2018
DOI: 10.1080/15476286.2018.1481695
|View full text |Cite
|
Sign up to set email alerts
|

The plastid-nucleus located DNA/RNA binding protein WHIRLY1 regulates microRNA-levels during stress in barley (Hordeum vulgare L.)

Abstract: In this article a novel mechanism of retrograde signaling by chloroplasts during stress is described. This mechanism involves the DNA/RNA binding protein WHIRLY1 as a regulator of microRNA levels. By virtue of its dual localization in chloroplasts and the nucleus of the same cell, WHIRLY1 was proposed as an excellent candidate coordinator of chloroplast function and nuclear gene expression. Comparison of wild-type and transgenic plants with an RNAi-mediated knockdown of WHIRLY1 showed, that the transgenic plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 34 publications
(36 reference statements)
3
44
0
Order By: Relevance
“…It had been first identified as a TF inducing expression of PR genes in an SA‐dependent manner (Desveaux et al ), making it an ideal candidate for retrograde signaling during senescence. Barley plants with an RNAi‐mediated WHIRLY1 knockdown are compromised in responding to environmental changes because of a reduced capability to synthesize micro‐RNA (Swida‐Barteczka et al ). When exposed to high irradiance, the WHIRLY1‐deficient plants show retarded senescence in comparison to the wild type that is able to accelerate senescence processes in response to environmental cues such as high light (Kucharewicz et al ).…”
Section: Retrograde Signaling In the Control Of Senescencementioning
confidence: 99%
“…It had been first identified as a TF inducing expression of PR genes in an SA‐dependent manner (Desveaux et al ), making it an ideal candidate for retrograde signaling during senescence. Barley plants with an RNAi‐mediated WHIRLY1 knockdown are compromised in responding to environmental changes because of a reduced capability to synthesize micro‐RNA (Swida‐Barteczka et al ). When exposed to high irradiance, the WHIRLY1‐deficient plants show retarded senescence in comparison to the wild type that is able to accelerate senescence processes in response to environmental cues such as high light (Kucharewicz et al ).…”
Section: Retrograde Signaling In the Control Of Senescencementioning
confidence: 99%
“…MicroRNA production is impaired under continuous high-light conditions in the barley WHIRLY1 knockdown mutant. WHIRLY1 is a DNA/RNA binding protein, but the exact function of WHIRLY1 in the microRNAs biogenesis is not known [169].…”
Section: Induced Senescence Pathways Involve Micrornasmentioning
confidence: 99%
“…Due to their dual-location and function in the nucleus and plastids (Krause et al, 2009), it has been supposed that WHIRLY1 could move from plastid to the nucleus (Isemer et al, 2012). The plastid isoform of WHIRLY1 affects the miRNA biogenesis in the nucleus (Swida-Barteczka et al 2018). Previously, we showed that the WHY1 protein can be phosphorylated by CIPK14 kinase or oxidized by H 2 O 2 , leading to different subcellular localization in the nucleus or in plastids, respectively (Ren et al 2017; Lin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…WHY1 protein binds for example to the promoter of WRKY53 and repress WRKY53 and WRKY33 expression in a development-dependent manner during early senescence in Arabidopsis (Miao et al 2013; Ren et al 2017), while it activates the HvS40 gene during natural and stress-related senescence in barley ( Hordeum vulgare ) (Krupinska et al 2013) and PsbA gene expression in response to chilling treatment in tomato (Zhuang et al 2018). In the nucleus, WHY1 protein also modulates telomere length by binding to their AT -rich region (Yoo et al 2007) and affects microRNA synthesis (Swida-Barteczka et al 2018). Moreover, in chloroplasts, WHY1 has a function on organelle genome stability, facilitating accurate DNA repair (Cappadocia et al 2010, 2012; Lepage et al 2013) and affects RNA editing/splicing (Prikryl et al, 2008; Melonek et al 2010).…”
Section: Introductionmentioning
confidence: 99%